Implementasi Konsep “Addicted to Nusantara” dalam Perancangan Interior Pusat Komunitas Kopi - Isabella Christie; Diana Thamrin; Celline Junica Pradjonggo (Intra, 2019)
Coffee is the third most consumed beverage in the world. According to International Coffee Organization, Indonesian coffee ranks fourth best in the world because of its various and special taste. In past times, coffee is just a beverage to complete your activity, such as reading newspaper, late night activities, watching TV,etc. Nowadays, coffee becomes a trend and used in art. However, there aren’t enough facilities to embrace the creative coffee community, especially in Surabaya. The purpose of this interior design is to provide an interactive and educative  Coffee Community Center interior to increase the sales and potential of local coffee. The design method used is Design Thinking which consist of understanding, observe, point of view, prototype, test and implementation. The design result is a Noesantara Coffee Community Center designed with the concept of “addicted to Noesantara”, which means to attract the visitor so that they become addicted to the place and interested to come back. Using a layout with mixed circulation, where the coffee gallery is used as the center to direct the visitors to another room, such as coffee shop, coffee bath and spa, workshop area, coffee roaster and tasting room, etc to increase the potential of Indonesian local coffee.